Characterization and mapping of NBS-LRR resistance gene analogs in apricot (Prunus armeniaca L.) - Soriano, J. M.; Vilanova, S.; Romero, Carlos; Llácer, Gerardo; Badenes, María L. (2017)
Genomic DNA sequences sharing homology with the NBS-LRR (nucleotide binding site-leucine-rich repeat) resistance genes were isolated and cloned from apricot (Prunus armeniaca L.) using a PCR approach with degenerate primers designed from conserved regions of the NBS domain. Restriction digestion and sequence analyses of the amplified fragments led to the identification of 43 unique amino acid sequences grouped into six families of resistance gene analogs (RGAs). All of the RGAs identified belong to the Toll-Interleukin receptor (TIR) group of the plant disease resistance genes (R-genes). RGA-specific primers based on non-conserved regions of the NBS domain were developed from the consensus sequences of each RGA family. These primers were used to develop amplified fragment length polymorphism (AFLP)-RGA markers by means of an AFLP-modified procedure where one standard primer is substituted by an RGA-specific primer. Using this method, 27 polymorphic markers, six of which shared homology with the TIR class of the NBS-LRR R-genes, were obtained from 17 different primer combinations. Of these 27 markers, 16 mapped in an apricot genetic map previously constructed from the self-pollination of the cultivar Lito. The development of AFLP-RGA markers may prove to be useful for marker-assisted selection and map-based cloning of R-genes in apricot.